Strategi Komunikasi Tentara dalam Upaya Membantu Pengamanan Pilkades Serentak di Kabupaten Ciamis - Endik Hidayat; Daniel Susilo; Teguh Anggoro (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
This research elaborates on the communication strategy of the security forces, especially the military, in assisting the Ciamis local government, the activity in question is the holding of simultaneous head elections. Because there are still few studies on the military in Indonesia, the location research in Ciamis tries to fill this gap. The unit of analysis used is the theory of mass communication and the concept of communication strategy. This study uses a qualitative focus method on the phenomenon of simultaneous village head elections in 72 villages in Ciamis Regency. This study found that there are two categories of military strategic communications. First, a social communication strategy that is open and closed or called clandestine. Second, mass media and social media communication strategy. There were two important events that were able to attract the attention of the public and the mass media, namely during the readiness call for the security forces for the village head election on March 25 2022 and the holding of simultaneous elections for 72 villages on March 27 2022